Development of Predictive Maintenance Model for N-Component Repairable System Using NHPP Models and System Availability Concept. (February 2016) - Srivastava, Nishit Kumar; Mondal, Sandeep
The technologically intensive nature of the predictive maintenance (PdM) method restricts its use to companies with higher turnover. This research is aimed to propose a PdM model for an N-component repairable system by integrating non-homogeneous Poisson process (NHPP) models and a system availability concept such that the use of technology is minimized, thereby extending its applicability to companies with lower turnover. It is known that manufacturing systems show reliability degradation with repeated overhauls and component replacements. This has the effect that the mean time between failures (MTBF) is non-identically distributed. Hence, the failure pattern of each component is analyzed using NHPP models and the mean system availability is calculated, which is now compared with the threshold system availability deciding the overall maintenance of the system. Further, the developed model is validated on a wheat flour mill.